2014
DOI: 10.1152/ajplung.00095.2013
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of airway cilia results in noninflammatory bronchiectasis and hyperreactive airways

Abstract: PD. Deletion of airway cilia results in noninflammatory bronchiectasis and hyperreactive airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…This interpretation is consistent with findings in other mouse models that exhibit defective mucus transport but lack a mucus-adhesive component, e.g. , models of primary ciliary dyskinesia (PCD), which also exhibit a mild lower airway phenotype 3133 .…”
Section: Discussionsupporting
confidence: 91%
“…This interpretation is consistent with findings in other mouse models that exhibit defective mucus transport but lack a mucus-adhesive component, e.g. , models of primary ciliary dyskinesia (PCD), which also exhibit a mild lower airway phenotype 3133 .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, a loss of airway cilia mobility was associated with an increase in airway reactivity in mice [35]. In the airways of individuals who have asthma, some areas of epithelial basement membrane seem to be denuded of ciliated cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Gilley and colleagues reported that conditional deletion of motile cilia in the lung of the adult mouse results in slower cilia beating frequency and the development of bronchiectasis (23). They found that airway dilation in bronchiectasis was due to morphological changes of airway epithelial cells with cellular hyperplasia and proliferation of club cells, and led to loss of cilia and MCC impairment.…”
Section: Discussionmentioning
confidence: 99%